Knowledge on rotavirus and pneumococcal vaccines among mothers of under five children - Muppidathi, Subbiah; Boj, Jenitha; Deivanayagam, Saminathan (International Journal of Contemporary Pediatrics, 2017)
Background: Childhood vaccines are one of the great triumphs of modern medicine. They are undoubtedly the most cost-effective healthcare interventions. Knowledge, attitude, and practices regarding the vaccines administered under the National Immunization Programme have been studied in different settings; however, studies regarding Rota virus and Pneumococcal vaccines in India are scarce. The Objective of the study was to assess the mothers’ knowledge on Rota virus and Pneumococcal vaccines and to identify the reasons for non-administration of these vaccines. Methods: This study is a cross-sectional study conducted in pediatric immunization clinic of Chennai Medical College Hospital and Research Centre from February to April 2017. About 380 parents were interviewed with a preformed structured questionnaire. Results: Of 380 respondents, 130 (34.2%) mothers were aware about Rotavirus vaccine and 148 (39%) about Pneumococcal vaccine. Awareness for these vaccines was seen high among middle and upper socio-economic group mothers. Among the mothers who were aware about these vaccines, the major source of information was doctors followed by health workers and media. Of 380 respondents only 66 (17%) mothers had administered Rotavirus vaccine and 75 (19.7%) had administered Pneumococcal vaccine. The reason for not administering these vaccines was lack of awareness. 274 (87.2%) mothers were not aware about Rotavirus vaccine and 261 (85.6%) mothers were not aware about pneumococcal vaccine. Conclusions: Present study found that most of the mothers were not aware about these live saving vaccines and they need to be educated about these vaccines through health workers or intense campaigning by using mass media.